Intra- and Inter-Rater Reliability of Ultrasound Measurements of Supraspinatus Tendon Thickness, Acromiohumeral Distance, and Occupation Ratio in Patients With Shoulder Impingement Syndrome - Fatih BAĞCIER,; Duygu GELER KÜLCÜ,; Elem YORULMAZ,; Elif Çiğdem ALTUNOK, (Archives of Rheumatology, 2020)
Objectives: This study aims to evaluate the intra- and inter-rater reliability coefficients of the supraspinatus tendon thickness, acromiohumeral distance, and occupation ratio in patients with shoulder impingement syndrome. Patients and methods: The study included 83 patients (21 males, 62 females; mean age 51.6±11.0 years; range, 26 to 70 years) with shoulder impingement syndrome. The supraspinatus tendon thickness, acromiohumeral distance, and occupation ratio values were obtained one week apart by two observers. The intraclass correlation coefficient (ICC), minimum detectable change, and standard error of measurement were calculated. Results: The first observer had excellent intra-rater reliability in all measurements (ICC >0.90) with minimum detectable change of 0.740-0.047 mm and standard error of measurement of 0.017-0.26 mm. The second observer had excellent intra-rater reliability in supraspinatus tendon thickness and acromiohumeral distance measurements (ICC >0.90) with minimum detectable change of 0.498-0.770 mm and standard error of measurement of 0.18-0.28 mm and good intra-rater reliability in the occupation ratio measurement (ICC; 0.75-0.90) with minimum detectable change of 0.060 mm and standard error of measurement of 0.022 mm. Inter-rater reliability coefficients were 0.916 (95% confidence interval [CI]; 0.873-0.945) for supraspinatus tendon thickness, 0.943 (95% CI; 0.914-0.963) for acromiohumeral distance with minimum detectable change of 0.673 mm and standard error of measurement of 0.243 mm and 0.790 (%95 CI; 0.693-0.853) for occupation ratio with minimum detectable change of 0.077 mm and standard error of measurement of 0.028 mm. Conclusion: These findings suggest that ultrasonographic measurements of the supraspinatus tendon thickness, acromiohumeral distance and occupation ratio can be reliable and consistent for clinical evaluation of patients with shoulder impingement syndrome in terms of supporting diagnosis and monitoring the treatment effect.